PENGARUH WAKTU FERMENTASI TERHADAP VOLUME GAS BIO DAN PENYISIHAN COD DENGAN METODE PERLAKUANAWAL MENGGUNAKAN KALIUMHIDROKSIDA(KOH) PADA ECENG GONDOK (Eichhornia crassipes) - Setiaty Pandia; Amin Trisnawati (Talenta Publisher (Universitas Sumatera Utara), 2016)
The purpose of this study was to determine the effect of alkali pre-treatment methods on the quality and quantity of biogas. The study was doneby fermentation process the water hyacinth with KOH in a concentration of 6,7 M; 4 M;3 M; and 2,95 (M) with water in ratio hyacinth: water 70:30; 50:50; 30:70 and 100:0 (v/v) mixed with cow dung starter in an anaerobic digester batch system of 2,5 L capacity. In this study the highest biogas production at KOH concentration 4 M was in ratio of 50:50 (v/v)with yield biogas volume 449 mL and 86,52% of COD revomal, 92,42% of TSS removal. The lowest biogas production at KOH concentration 6,7 M was in ratio of 70:30 (v/v) with yield biogas volume 132 mL and 86,55% of COD removal and 88,65%of TSS removal.